A Quarterthiophene-Based Dye as an Efficient Interface Modifier for Hybrid Titanium Dioxide/Poly(3-hexylthiophene)(P3HT) Solar Cells - Pirashanthan, A.; Murugathas, T.; Robertson, N.; Ravirajan, P.; Velauthapillai, D. (University of Jaffna, 2019)
This work focused on studying the influence of dyes, including a thiophene derivative dye with a cyanoacrylic acid group ((E)-2-cyano-3-(30 ,300,3000-trihexyl-[2,20 :50 ,200:500,2000- quaterthiophene]- 5-yl) acrylicacid)(4T), on the photovoltaic performance of titanium dioxide (TiO2)/poly(3-hexyl thiophene)(P3HT) solar cells. The insertion of dye at the interface improved the efficiency regardless of the dye used. However, 4T dye significantly improved the efficiency by a factor of three when compared to the corresponding control. This improvement is mainly due to an increase in short circuit current density (JSC), which is consistent with higher hole-mobility reported in TiO2/P3HT nanocomposite with 4T dye. Optical absorption data further revealed that 4T extended the spectral response of the TiO2/P3HT nanocomposite, which could also enhance the JSC. The reduced dark current upon dye insertion ensured the carrier recombination was controlled at the interface. This, in turn, increased the open circuit voltage. An optimized hybrid TiO2/P3HT device with 4T dye as an interface modifier showed an average efficiency of over 2% under-simulated irradiation of 100 mWcm−2 (1 sun) with an Air Mass 1.5 filter
Keywords: Hybrid solar cells; Titanium dioxide; Poly(3-hexylthiophene); Oligothiophene dye; Interface modifier; Photovoltaic; Absorption; Quantum efficiency; Polymers; Efficiency